Fencing - Turner, A.; Fulcher, D.; Weaver, S.; Marshall, G. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Given the repetitive demand to effectively execute lunging and changes in direction within fencing, the ability to sustain these at maximal Capacity is fundamental to performance, and describesa fencer`s speed and power endurance Capacity. Due to the requirement to stand in an asymmetrical position, inducing potential asymmetries, strength training is necessary for both performance enhancement and injury avoidance. Strength and power lift variations, including unilateral exer- cise, are fundamental to support this, coupled with ballistic training and plyometric exercise, again with a focus upon unilateral jumps with emphasis on landing mechanics. Conditioning should be conversant to the differing W:R between weapon types; however, consideration of exposing athletes to "worst case scenario" must be applied. Performing high intensity interval training is recommended, particularly involving unloaded modes of exercise (bike, row, battle ropes) in order to evoke high blood lactate response and develop adaptations surrounding tolerance and recovery from continuous explosive exercise. Finally, programming should be mindful towards exercises that favour the posterior chain, to both promote horizontal force application and address relative weakness in comparison to anterior musculature. The lack of acute (within competition) fatigue may not be surprising given the format of a fencing competition, which provides ample opportunity for recovery. In fact, and assuming consistent psychological stress and appropriate nutrition it should be conceivable that fencers can fence at maximal intensity throughout the duration of the competition. Subsequently, and beyond strength and conditioning practices, the sport science support teams of these athletes should investigate various recovery strategies around fuel and fluid replacement (i.e., nutrition) and psychological interventions to cope with the high stress that may in turn increase intensity and fatigue. Also, post competition strategies centering on reducing muscle damage and subsequent inflammation should be investigated.